Desempeño laboral de los funcionarios del departamento de tesorería del Gobierno Autónomo descentralizado Parroquial Rural de Ricaurte (gadp) - Arroyo Castro, Andrea Carolina (2019)
The present case study is oriented to the analysis of the labor performance of the officials of the treasury department of the Rural Autonomous Decentralized Government of Ricaurte (GADP), considering that the work performance performed by each official is of vital importance to the institution, the same which offers services to different people of the parish. Through the analysis of work performance in the treasury department, it is possible to know if a person is correctly fulfilling the tasks entrusted within their labor functions, or there is a factor that prevents them from performing their functions in the correct way, also through the The same will be known if the person is trained to perform the work of which he is in charge or if he needs a training or knowledge update, considering that every day there are different advances so that, in the different jobs people need to be trained every year or every so often. Within the labor analysis, it could also be considered as a factor that prevents a good performance, to the work environment that exists within a company or an institution, this helps notably for an employee to work motivatedly if there is a good work environment